The Effect of Teaching Coping Skills on the Anxiety in Caregivers of Patients with Cancer Undergoing Chemotherapy - Mahnaz Seyedolshohadayi; Parimehr Ayar; Marjan Mardani; Hamid Haghani (Iran University of Medical Sciences, 2016)
Background: Long-term hospitalization for cancer treatment can prevent the continuation of a normal life of patients with cancer and their families. In this regard, caregivers face with problems such as psychological stress, hopelessness, fear, anxiety, and feelings of depression. The aim of this research was to investigate the effect of teaching of coping skills on the anxiety in caregivers of patients with cancer undergoing chemotherapy. Methods: This research was a quasi-experimental study, pretest-posttest design with control group which started from October 2014 and lasted until February 2015. In this study, 62 caregivers of cancer patients were selected by convenience sampling method. A total of 30 subjects were non-randomly assigned in the experimental (intervention) group and 32 ones in the control group. The intervention was done based on a defined plan, which included teaching coping strategies to the experimental group in 4 sessions (45-60 minutes each session) using booklet and question and answer (QA) meeting. The control group received routine education. After 4 weeks, both groups were compared in terms of anxiety using Beck anxiety inventory questionnaire. The data were analyzed using SPSS 18 software, through performing paired t test, the Chi-square test, the Independent t-test, and Fisher's exact test. Results: There was no significant difference regarding the anxiety between the experimental and control groups before the intervention (P=0.122). Four weeks after the intervention, anxiety of the experimental group improved, but no improvement was observed in the control group. Therefore, the two groups had statistically significant differences in this regard (P=0.001). Conclusion: With regard to anxiety of the caregivers of the patients with cancer undergoing chemotherapy, the results showed the effectiveness of intervention i.e., teaching coping skills. Considering the effectiveness of teaching coping skills and consequently decreased anxiety in the caregivers of patients with cancer patients undergoing chemotherapy, it is suggested that this intervention be included in nurses family-centered care program.